Membrane Destabilization Induced by Lipid Species Increases Activity of Phosphorothioate-Antisense Oligonucleotides - Shiyu Wang; Nickolas Allen; Xue-hai Liang; Stanley T. Crooke (Elsevier, 2018)
Chemically modified antisense oligonucleotides with phosphorothioate linkages (PS-ASOs) mediate site-specific cleavage of RNA by RNase H1 and are broadly used as research and therapeutic tools. PS-ASOs can enter cells via endocytic pathways and escape from membrane-enclosed endocytic organelles to reach target RNAs. We recently found that lysobisphosphatidic acid is required for release of PS-ASOs from late endosomes. Here, we evaluated the effects of other lipids on PS-ASO intracellular trafficking and activities. We show that free fatty acids, ceramide, and cholesterol increase PS-ASO activities. Free fatty acids induced formation of lipid droplets without changing the intracellular localization of PS-ASOs in early or late endosomes. Ceramide and cholesterol did not obviously induce the formation of lipid droplets, but cholesterol caused enlargement of endosome size and volume. Although none of those lipids appeared to influence PS-ASO internalization or intracellular trafficking processes, all led to an increase in leakiness of late endosomes. Thus, the membrane destabilization induced by these lipids likely contributes to PS-ASO release from late endosomes, which, in turn, increases PS-ASO activity. Keywords: antisense oligonucleotides, free fatty acids, ceramide, cholesterol, intracellular trafficking, endosomal leakiness